(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2019)
This research aims to develop a practical guide-book of scientific approach that can develop college students scientific thinking skills. The research is using the Research and Development (R & D) form by follow development path of ADDIE (Analyze Design, Develop, implement and Evaluate). The result of validation from the education and the chemistry experts showed that the practical guide-book that where develop was valid and possible to use. Then the practical guide-book is implemented into learning and the results showed that there are differences in students’ scientific thinking skills before and after the developed practical guide-book are implemented and there is an increase with a normal gain score is 0.76 which is in the high category and students respond positively to practical activities using scientific-based practical guide-book. Thus it can beconcluded that the developed practical guide-book is valid and possible to use and can develop students’ scientific thinking skills